Sulfate reducing bacteria and acetoclastic methanogens for process intensification of anaerobic digestion - Piccolo, Nicholas (My University, 2020)
Anaerobic digestion (AD) is an essential process in wastewater treatment to stabilize waste organic solids and produce biogas. This research is comprised of two projects in the discipline of anaerobic digestion. First, the effect of high sulfate concentration on anaerobic digestion of wastewater sludge was investigated. Secondly, the performance of acetoclastic methanogens Methanosaeta spp. and Methanosarcina spp. were investigated under intensified AD operation conditions (i.e., elevated acetate concentrations, vigorous mixing, etc.). In the sulfate experiments, the cumulative biogas and methane production decreased linearly with increasing initial sulfate doses (0 – 3,300 mg S L-1) and the correlation between the sulfate dose and methane production was verified with theoretical predictions, indicating complete reduction of sulfate to sulfide in AD. The examined sulfate concentrations resulted in no clear negative effects on the COD (chemical oxygen demand) removal or VSS (volatile suspended solids) destruction of the wastewater sludge, indicating that previous findings on sulfide toxicity might have been attributed to potential COD overestimation of digested sludge with high levels of sulfide. To avoid potential misinterpretation of AD performance on sulfide toxicity effects, we proposed a new method for COD correction for digested sludge. In the second project focused on acetoclastic methanogens, vigorous mixing conditions substantially decreased Methanosarcina spp. growth and methane production, and the decreased methanogenesis was more pronounced at higher acetate concentrations. Methanosarcina spp. prefer to grow in clusters and the vigorous mixing can disrupt cluster formation; as a result, reduced chances for cluster formation limited the growth of Methanosarcina spp.. While Methanosarcina spp. growth and methane production increased with the increasing acetate concentration, Methanosaeta spp. growth was unaffected by the examined vigorous mixing and soluble substrate conditions with negligible relative growth. Thus, rapid enrichment of Methanosarcina spp. is critical for successful operation intensified of AD processes under high organic loading conditions.
Keywords: Anaerobic Digestion; Sulfate Reduction; Acetoclastic Methanogenesis; Process Intensification